1998
DOI: 10.1023/a:1006936431276
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to elucidate the relationship between glycosylation of IgG and aging, oligosaccharide structures of human IgG purified from sera of men and women aged 18 to 73 years were investigated. Oligosaccharides were liberated quantitatively from IgG by hydrazinolysis followed by N-acetylation and were tagged with p-aminobenzoic acid ethyl ester. The oligosaccharide structures were then analyzed by HPLC in conjunction with sequential exoglycosidase digestion. All IgG samples were shown to contain a series of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 25 publications
10
31
0
Order By: Relevance
“…Indeed, previous studies have shown an age-dependent increase in sG0/G1 (5557). Here, in addition to age, we used a series of multivariate analyses to assess the impact of CCP, disease duration and gender on the sG0/G1:DAS correlation.…”
Section: Resultsmentioning
confidence: 90%
“…Indeed, previous studies have shown an age-dependent increase in sG0/G1 (5557). Here, in addition to age, we used a series of multivariate analyses to assess the impact of CCP, disease duration and gender on the sG0/G1:DAS correlation.…”
Section: Resultsmentioning
confidence: 90%
“…An optimized tryptic cleavage procedure was applied (23), and no tryptic missed cleavages were observed. On the basis of literature knowledge of IgG N -glycosylation (2731) the nanoliquid chromatography-electrospray ionization (LC-ESI-MS) method allowed unambiguous assignment of 46 IgG glycopeptides species (18 glycoforms of IgG1, 10 of IgG4, and 18 of IgG2; Table II). Glycoforms having 5 N -acetylhexosamine residues were interpreted as bisected species (2731).…”
Section: Resultsmentioning
confidence: 99%
“…Data processing and evaluation were performed with FlexAnalysis Software (Bruker Daltonics) and Microsoft Excel, respectively. Structural assignment of the detected glycoforms was performed on the basis of literature knowledge of IgG N -glycosylation (27–32). The data were baseline subtracted and the intensities (peak heights) of a defined set of 27 glycopeptides (16 glycoforms for IgG1 and 11 for IgG2&3) were automatically defined for each spectrum as described before (33).…”
Section: Methodsmentioning
confidence: 99%
“…Structural assignment of the detected glycoforms was performed on the basis of literature knowledge of IgG N -glycosylation (27–32). Relative intensities of 20 IgG1, 20 IgG2/3, and 10 IgG4 glycopeptide species were obtained by integrating and summing the first three isotopic peaks of both doubly and triply charged glycopeptides species followed by background correction and normalization to the total IgG subclass specific glycopeptide intensities.…”
Section: Methodsmentioning
confidence: 99%